Lonicerin attenuates house dust mite-induced eosinophilic asthma through targeting Src/EGFR signaling - Deng, Zhenan; Zhang, Xuefei; Wen, Junjie; Yang, Xiaojing; Xue, Lingna; Ou, Changxing; Ma, Jianjuan; Zhan, Hongrui; Cen, Xiaomin; Cai, Xuliang; Zhang, Yu; Chen, Riken; et al. (Frontiers in Pharmacology, 2022)
Eosinophilic asthma is the predominant phenotype of asthma, and although these patients are sensitive to glucocorticoid therapy, they also experience many side effects. Lonicerin is a kind of bioflavonoid isolated from the Chinese herb Lonicera japonica Thunb, which has anti-inflammatory and immunomodulatory effects. The aim of this study was to elucidate the effects of lonicerin on eosinophilic asthma and its potential mechanisms. Here, we established a house dust mite (house dust mite)-induced eosinophilic asthma model in BALB/c mouse, and evaluated the effects of lonicerin on it. Our results showed that lonicerin significantly reduced airway hyperresponsiveness the number of inflammatory cells (especially eosinophils) and the elevation of interleukin (IL)-4, IL-5, IL-13 and eotaxin in bronchoalveolar lavage fluid (BALF) supernatants of mice. Additionally, lonicerin also eminently blunted inflammatory infiltration and mucus secretion, as well as mRNA levels of Mucin 5AC (MUC5AC) in lung tissue. Furthermore, results of network pharmacology and molecular docking revealed that Src kinase and epidermal growth factor receptor may be the potential targets responsible for the effects of lonicerin. Finally, in vivo experiments confirmed that lonicerin inhibited activation of the Src/EGFR pathway by decreasing their phosphorylation. Taken together, the present study demonstrated that lonicerin could suppress HDM-induced eosinophilic asthma in mice through inhibiting the activation of Src/EGFR pathway, which also provides a basis for further research as a new potentially therapeutic agent for eosinophilic asthma and its underlying mechanisms in the future.